2021
DOI: 10.3390/ani11041009
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes towards Mules in a Group of Soldiers

Abstract: Mules are essential for pack work in mountainous areas, but there is a lack of research on this species. This study intends to assess the perceptions, attitudes, empathy and pain perception of soldiers about mules, to understand the type of human–mule relationship. For this, a survey was applied with closed-ended questions where the empathy and pain perception tools were included and later analyzed through correlations. Open-ended questions were analyzed through text mining. A total of 73 soldiers were surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Research conducted in Romania evaluated the same behavioral indicators and found that the prevalence of the horses' behavioral responses presented significant differences when the tests were applied by the owner or by an unknown evaluator (3). Other studies with similar tests obtained very different results (1,10,15), possibly because of aspects such as: a) the cognitive ability of horses and mules to recognize familiar humans (18,22), including facial recognition (23), and to remember specific experiences, especially bad ones (3), so it would be logical to obtain different reactions from the animals depending on the familiarity with the person performing the test; b) previous human-equine interactions, which when negative, can lead the animal to have excessive fear reactions, which can limit their use and make them dangerous for the conditions of the handlers (24) in which the test is performed (work routine, strange environment (10); d) individual temperament traits of the animals (3); e) the living environment (resources provided, tasks and demands of the work, climatic conditions, and geo-cultural characteristics, among others) (25); f) genetic characteristics and hybrid vigor, greater cognitive and endurance capacities of mules compared to horses are described (26), g) the experience and training of the observer for the evaluation of behavior and some health indicators such as body condition (27), among other aspects. In future studies, we consider it relevant to perform a comparative evaluation of the behavior of horses and mules in front of an unknown evaluator and the owner to control for possible measurement biases that could have occurred.…”
Section: Behavioral Indicatorsmentioning
confidence: 82%
“…Research conducted in Romania evaluated the same behavioral indicators and found that the prevalence of the horses' behavioral responses presented significant differences when the tests were applied by the owner or by an unknown evaluator (3). Other studies with similar tests obtained very different results (1,10,15), possibly because of aspects such as: a) the cognitive ability of horses and mules to recognize familiar humans (18,22), including facial recognition (23), and to remember specific experiences, especially bad ones (3), so it would be logical to obtain different reactions from the animals depending on the familiarity with the person performing the test; b) previous human-equine interactions, which when negative, can lead the animal to have excessive fear reactions, which can limit their use and make them dangerous for the conditions of the handlers (24) in which the test is performed (work routine, strange environment (10); d) individual temperament traits of the animals (3); e) the living environment (resources provided, tasks and demands of the work, climatic conditions, and geo-cultural characteristics, among others) (25); f) genetic characteristics and hybrid vigor, greater cognitive and endurance capacities of mules compared to horses are described (26), g) the experience and training of the observer for the evaluation of behavior and some health indicators such as body condition (27), among other aspects. In future studies, we consider it relevant to perform a comparative evaluation of the behavior of horses and mules in front of an unknown evaluator and the owner to control for possible measurement biases that could have occurred.…”
Section: Behavioral Indicatorsmentioning
confidence: 82%
“…Donkeys have played an essential role in developing human civilizations (1). There are approximately 50.5 million donkeys globally (2), benefiting around 600 million people and playing a vital role in the livelihood of poor and vulnerable communities in lower-middle income countries (LMICs) (1,(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Donkeys have played an essential role in developing human civilizations (1). There are approximately 50.5 million donkeys globally (2), benefiting around 600 million people and playing a vital role in the livelihood of poor and vulnerable communities in lower-middle income countries (LMICs) (1,(3)(4)(5)(6)(7). The importance of working donkeys for their owner's livelihoods and the economies of developing countries is well known (3,5,7); for example, in Senegal, draft donkeys contribute 74% of their driver's annual income (8).…”
Section: Introductionmentioning
confidence: 99%
“…Donkeys have played an essential role in developing human civilizations (1). There are approximately 50.5 million donkeys globally (2), benefiting around 600 million people and playing a vital role in the livelihood of poor and vulnerable communities (1,3,4). The importance of working donkeys for their owner's livelihood and the economies of developing countries is well known (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Donkeys have played an essential role in developing human civilizations (1). There are approximately 50.5 million donkeys globally (2), benefiting around 600 million people and playing a vital role in the livelihood of poor and vulnerable communities (1,3,4).…”
Section: Introductionmentioning
confidence: 99%